KELOMPOK MUSIK REJUNG PESIRAH: STRATEGI ADAPTASI PADA MASYARAKAT PALEMBANG - Dwi Putri Agustini (Tonika: Jurnal Penelitian dan Pengkajian Seni, 2019)
The present phenomenon has clearly brought a change and the influence of the development of traditional music in Palembang society, if this is not carefully addressed, it will experience a shift, alienation and even lose its supporters. The rejung pesirah music group is one of the music groups that still maintains traditional arts in the people of Palembang. This study examines how the adaptation strategy of the rejung pesirah music group in dealing with changes and developments in Palembang society. For this reason, the approach used is cultural anthropology with qualitative case study research methods in Palembang. Data collection is done through observation, interviews and document studies that use triangulation techniques as the validation of the data, while for data analysis through content analysis and interactive models. The results showed that the adaptation strategy undertaken by the rejung pesirah music group was an act and creative ability and had a positive mindset, understanding in responding to changes and needs as an impulse to develop in the face of environmental change and development through learning processes and cultural modification, which resulted a creativity that is the creation of songs, musical arrangements, and musical instruments in the rejung pesirah music group.